Managerial Communication Processes In Networked Radio (Case Study At PT Radio Rajawali Terbang) - Tania Putri; Noning Verawati; Wawan Hernawan (Cita konsultindo, 2026)
Communication patterns refer to the form of relationships between two or more individuals in the process of sending and receiving messages, which are associated with two components: a framework or plan that includes the steps of an activity, and components that play an important role in establishing communication relationships between individuals or groups. The purpose of this research is to identify the managerial communication pattern within the existence of PT Radio Rajawali Terbang and to understand the condition of managerial communication led by a single leader who must manage three regions in Lampung Province, namely Bandar Lampung City, Metro City, and Kotabumi, North Lampung. As a result, several branches have experienced a decline in work effectiveness, a lack of program innovation, and limited cross-location collaboration. This research used a qualitative method, aiming to explore, collect, and analyze information in depth. The data collection techniques used in this study were observation, in-depth interviews, and documentation. The validity test in this study employed triangulation, specifically technique triangulation and source triangulation.